Self-compassion and death distress among individuals affected by the February 6, 2023, Türkiye Earthquake: The mediating role of doomscrolling and resilience - Kaya, Yagmur; Osmanoglu, Naile; Satici, Seydi Ahmet; Deniz, M. Engin (SAGE PUBLICATIONS LTD, 2025)
Large-scale events like natural disasters and epidemics can have significant impacts on individuals' mental health worldwide. Thus, it is crucial to examine the psychological effects of such events on people. This study aimed to investigate the relationship between self-compassion, death distress, doomscrolling, and resilience, among individuals affected by earthquakes. A total of 364 Turkish adults affected by the earthquakes that occurred in T & uuml;rkiye on February 6, 2023, participated in the study. Structural equation modeling was utilized to explore the mediating roles of doomscrolling and resilience in the association between self-compassion and death distress. The results of the structural equation modeling indicated that both doomscrolling and resilience mediated the relationship between self-compassion and death distress in earthquake-affected individuals. These findings contribute to understanding the interplay between self-compassion, death distress, doomscrolling, and resilience in the context of earthquakes and are expected to inform future research endeavors.
Keywords: death distress; doomscrolling; earthquake; resilience; self-compassion; SURVIVORS; DISASTER; TRAUMA; HEALTH; SCALE; Psychology